Competition law and affirmative action in Malaysia: complementarity or conflict? - Ahamat, Haniff; Abdul Rahman, Nasarudin; Mohamed, Abdul Majid Hafiz (UPM Press, 2015)
This paper examines the interface between competition law and affirmative action in Malaysia. It analyses the different goals of competition law and explains how that may accommodate Malaysia’s race-based affirmative action programme (or also known as the pro-Bumiputera policies) introduced via the New Economic Policy (NEP) post 1969 racial riot and adopted in 1971. This paper finds Malaysian competition legislative enactment, that is the Competition Act 2010 (CA 2010), does not make any explicit reference to Malaysia’s affirmative policies. Based on an analysis of the existing provisions of the CA 2010, this paper finds that Chapters 1 and 2 prohibitions can be used against `ethnic cartels’ which have the effect of preventing Bumiputera enterprises from participating in the market. This is by allowing the CA 2010 to open up the market to those enterprises providing them the opportunity to participate at all levels of production chain and putting an end to the phenomenon that they have to crowd into the least profitable level.